Rotational Thromboelastometry in Neonates Admitted to a Neonatal Intensive Care Unit: A Large Cross-sectional Study - Sokou, Rozeta; Tsantes, Andreas G.; Konstantinidi, Aikaterini; Ioakeimidis, Georgios; Lampridou, Maria; Parastatidou, Stavroula; Theodoraki, Martha; Piovani, Daniele; Iliodromiti, Zoe; Boutsikou, Theodora; Iacovidou, Nicoletta; Douramani, Panagiota; Poulis, Aristarchos; Kokoris, Styliani; Kriebardis, Anastasios G.; Bonovas, Stefanos; Tsantes, Argirios E. (Seminars in Thrombosis and Hemostasis, 2021)
The aim of the present study was to assess the coagulation profile in neonatal critical illness using rotational thromboelastometry (ROTEM), and to investigate its association with disease severity and its potential prognostic role in this clinical setting. Over a period of 67 months (July 2014–February 2020) 423 critically ill neonates with confirmed or suspected sepsis, perinatal hypoxia, or respiratory distress syndrome, hospitalized in our neonatal intensive care unit were included in the study. Demographic, clinical, and laboratory data were recorded on admission day and arterial blood was analyzed on ROTEM analyzer using the standard extrinsically activated rotational thromboelastometry assay (EXTEM). Neonatal illness severity scores (Modified NEOMOD [Neonatal Multiple Organ Dysfunction] and SNAPPE [Score for Neonatal Acute Physiology with Perinatal Extension]) were calculated at the same time as ROTEM analysis. Mortality during in-hospital stay was the main outcome measure. Multivariable analyses showed that a 10 mm decrease in EXTEM clot amplitude recorded at 10 minutes (A10) is significantly associated with a higher mortality (odds ratio [OR] = 1.69, 95% confidence interval [CI]: 1.33–2.08). Higher modified NEOMOD (OR = 1.36, 95% CI: 1.26–1.47) and higher SNAPPE scores (OR = 1.06, 95% CI: 1.04–1.08) were also associated with increased mortality. The CT and A10 variables demonstrated the best prognostic performance among the EXTEM parameters for mortality (area under the curve [AUC] = 0.78; 95% CI: 0.69–0.86 and AUC = 0.76; 95% CI: 0.66–0.85, respectively), showing an optimal cut-off CT ≥63 seconds and A10 ≤37 mm. Using optimal cut-off values of the EXTEM parameters for prediction of mortality, neonates with CT ≥63 seconds were 7.4 times more likely to die (OR = 7.40, 95% CI: 3.50–15.65), while neonates with A10 ≤37 mm were 5.8 times more likely to die (OR = 5.88, 95% CI: 2.94–12.50). An EXTEM hypocoagulable profile on disease onset was shown to be an independent risk factor for in-hospital mortality in neonatal critical illness.
Keywords: thromboelastometry; ROTEM; prognosis; mortality; critically ill neonates